2019
DOI: 10.1186/s13037-019-0195-3
|View full text |Cite
|
Sign up to set email alerts
|

Inter-observer reliability of alternative diagnostic methods for proximal humerus fractures: a comparison between attending surgeons and orthopedic residents in training

Abstract: BackgroundProximal humerus fractures are frequent, and several studies show low diagnostic agreement among the observers, as well as an inaccurate classification of these lesions. The divergences are generally correlated with the experience of the surgeons as well as the diagnostic methods used. This paper challenges these problems including alternative diagnostic methods such as 3D models and augmented reality (holography) and including the observers’ period of medical experience as a factor.MethodsTwenty ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
2
14
0
1
Order By: Relevance
“…The 3D-models as a diagnostic method showed the highest agreement among interobservers for the treatment of proximal humerus fractures (overall Kappa coefficient), both among experts and residents. Higher concordance based on proximal humerus fractures classification was found using 3D-models in our previous work, when compared to x-ray, tomography or holography [ 13 ]. Although 3D-models were the diagnostic method with a higher agreement in the choice of treatment among all interobservers, experts showed overall higher agreement when compared to residents.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The 3D-models as a diagnostic method showed the highest agreement among interobservers for the treatment of proximal humerus fractures (overall Kappa coefficient), both among experts and residents. Higher concordance based on proximal humerus fractures classification was found using 3D-models in our previous work, when compared to x-ray, tomography or holography [ 13 ]. Although 3D-models were the diagnostic method with a higher agreement in the choice of treatment among all interobservers, experts showed overall higher agreement when compared to residents.…”
Section: Discussionmentioning
confidence: 78%
“…The classifications proposed by Charles Neer, 1970 [5] and the AO / OTA group -Arbeit Gemeinschaft für Osteosynthesefragen [6], the most widespread and used worldwide, were not able to find a relevant reproducibility for diagnosis of proximal humerus fractures [21][22][23]. It seems logical, therefore, that the best choice to treat patients has uncertainties [2,3,13]. Handoll et al [2] state that there is not enough evidence that surgical treatments are superior to conservative ones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future developments in diagnostic imaging include alternative tools such as 3D models and augmented reality (holography) [35]. Recently, Cocco et al reported better inter-and intraobserver agreement when 3D-printed models of the fractures were used to classify according to the Neer and the AO/OTA systems, compared with traditional CT scans and 3D reconstruction [36,37].…”
Section: Discussionmentioning
confidence: 99%